GC Tooth Mousse Plus: A potential storage media for avulsed teeth - Sundeep K Hegde; Sham S Bhat; Sharan S Sargod; Ajay Rao; Nanditha Hegde (Archives of Medicine and Health Sciences, 2016)
Context: Avulsion injury is a severe form of dental trauma. Due to the complexity of this injury, the neurovascular supply is severely compromised and usually results in the loss of pulp vitality. A variety of factors can influence the success of replantation especially the storage media and storage period. Casein phosphopeptides are derived from casein which accounts for 80% of the total protein in bovine milk. They can function as carriers for several minerals especially calcium and also have known to have antibacterial properties. Aim: The purpose of this study is to evaluate the efficacy of GC Tooth Mousse Plus in comparison with chilled Homogenous pasteurized whole milk as a storage media. Materials and Methods: Thirty healthy premolars that are extracted for orthodontic purpose will be divided into three groups: (1) Group A: Control (Saline), (2) Group B: Positive control (Chilled Homogenous milk), (3) Group C: Experimental (GC Tooth Mouse Plus). These groups were further divided into two subgroups, each indicating storage period of 30 min and 60 min. The periodontal ligament (PDL) cell viability will be checked using tryphan blue staining. Results: Data were analyzed using Student's t-test. Conclusion: GC Tooth Mousse Plus can be used as a storage media to prevent desiccation of PDL cells up to the duration of 60 min.